Why UK-trained doctors leave the UK: Cross-sectional survey of doctors in New Zealand - Sharma, A; Lambert, T; Goldacre, M (2012)
Objectives: To investigate factors which influenced UK-trained doctors to emigrate to New Zealand and factors which might encourage them to return. Design: Cross-sectional postal and Internet questionnaire survey. Setting: Participants in New Zealand; investigators in UK. Participants: UK-trained doctors from 10 graduation-year cohorts who were registered with the New Zealand Medical Council in 2009. Main outcome measures: Reasons for emigration; job satisfaction; satisfaction with leisure time; intentions to stay in New Zealand; changes to the UK NHS which might increase the likelihood of return. Results: Of 38,821 UK-trained doctors in the cohorts, 535 (1.4%) were registered to practise in New Zealand. We traced 419, of whom 282 (67%) replied to our questionnaire. Only 30% had originally intended to emigrate permanently, but 89% now intended to stay. Sixty-nine percent had moved to take up a medical job. Seventy percent gave additional reasons for relocating to New Zealand including better lifestyle, to be with family, travel/working holiday, or disillusionment with the NHS. Respondents' mean job satisfaction score was 8.1 (95% CI 7.9-8.2) on a scale from 1 (lowest satisfaction) to 10 (highest), compared with 7.1 (7.1-7.2) for contemporaries in the UK NHS. Scored similarly, mean satisfaction with the time available for leisure was 7.8 (7.6-8.0) for the doctors in New Zealand, compared with 5.7 (5.6-5.7) for the NHS doctors. Although few respondents wanted to return to the UK, some stated that the likelihood of doctors' returning would be increased by changes to NHS working conditions and by administrative changes to ease the process. Conclusions: Emigrant doctors in New Zealand had higher job satisfaction than their UK-based contemporaries, and few wanted to return. The predominant reason for staying in New Zealand was a preference for the lifestyle there.